Implementation of Capm, Fama-French Three-Factor, and Five-Factor in Indonesia Stock Exchange and Cement Industry Sector - Wedagama, Dewa Nyoman Wiryasantika; Hakim, Dedi Budiman; Juanda, Bambang; Andati, Trias (International Journal of Economics and Financial Issues, 2022)
Weighting Average Cost of Capital (WACC) plays a critical role as a discounting factor of the corporate valuation process’s estimated future free cash flow by highly influencing the valuation process. It consists of three components, namely cost of debt, cost of equity, and proportion of capital structure. Costs of debt and capital structure are easily calculated due to data stability and less volatility. Meanwhile, the cost of equity is difficult to determine due to assumption, the period taken, the method applied, and complexity. Many assets pricing methods are used to determine the required rate of return in equity, namely CAPM, Fama French Three-Factor (FF3F), and Fama French Five-Factor (FF5F). These three asset pricing models are used to determine the models with strong explanatory factors on equity return to portfolios developed from sorting FF5F factors and individual equity of four cement companies publicly listed in the Indonesia Stock Exchange (IDX).